Financial implications of relationship marketing in airline business - Dinçer, Hasan; Hacıoğlu, Ümit; Özdemir, Aydın (IGI Global, 2018)
Relationship marketing promises a change from vendor, product and price centered marketing concept to a new people, long-term relationships and value centered marketing concept for airline companies in search of a messiah who will rescue them from bleeding to death because of monopolized supply market, duplicated services, financial crises, heavy pressure of competition and low profit margins. In this chapter, definitions and short background of relationship marketing are revised by focusing on components of the concept and relations with customer loyalty, customer value and basic notions. A glance at the airline industry takes place with a focus on relationship marketing and airline business on the basis of implication aspects such as frequent flyer programs, global distribution systems and internet. Specifically, domains of relationship marketing concept on the airline business are analyzed in detail specific to cost and profitability balance.
Keywords: Trust; Relationship Quality; Relational Norms